Proteinuria. Issue 3 (March 2020) - Copeland, Lauren; Gillis, Keith
Measurement of urinary protein is an essential part of the evaluation of chronic kidney disease; it has both diagnostic and prognostic significance. Proteinuria is an independent risk factor for progression of renal disease, but is also independently associated with increased cardiovascular mortality. Despite its far-reaching implications, the definition, diagnosis and treatment of proteinuria can cause confusion in primary care. Early detection of proteinuria in the context of diabetes or otherwise is vital given the potential for intervention to reduce urinary protein losses and improve renal and cardiovascular outcomes. This article will focus on the definition, potential causes and management of proteinuria, including which individuals should be referred to secondary care.